Diversity, Distribution, and Community Structure of Wild Edible Mushrooms in Three Districts of Aceh Province - Mubarak, Albian; Putri, Elisa; Amilda, Putri (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Samudra, 2026)
Wild edible mushrooms are important components of terrestrial ecosystems, particularly in decomposition processes and nutrient cycling. This study aimed to analyze species diversity, distribution, and community structure of wild edible mushrooms in Aceh Selatan, Aceh Tengah, and Aceh Tamiang districts, Aceh Province. Mushroom inventories were conducted using a field walk survey with transect routes as sampling units in potential mushroom habitats. Species diversity was analyzed based on occurrence frequency using the Shannon–Wiener (H’), Margalef (DMg), and Pielou (J’) indices, while beta diversity was assessed using the Jaccard similarity index based on presence–absence data. A total of 10 wild edible mushroom species belonging to 9 families were recorded, exhibiting cosmopolitan, restricted, and unique distribution patterns. The highest species diversity was observed in Aceh Tengah (H’ = 1.963). Beta diversity analysis showed moderate to relatively high similarity among districts (J = 0.50–0.63), with the highest similarity between Aceh Tengah and Aceh Tamiang. Differences in community composition were associated with habitat characteristics, organic substrate availability, and microclimatic conditions.